The media’s role in political decision-making processes - Albæk, Erik; Green-Pedersen, Christoffer (Politica, 2020)
Do the media matter for public policy making? Based on the literature on the conditionality of the effect of mass media attention on political attention and theories of public policy making, this article argues that it depends on prior political attention. If the media focus on a case related to an issue to which politicians already pay attention, and the media attention is sustained, this can initiate a political decision-making process that leads to public policy change. The article illustrates this logic using two Danish examples and discusses how this argument can be investigated more broadly.